THE EFFECT OF SENSORY INTEGRATION THERAPY ON MOTOR PLANNING ABILITY IN CHILDREN WITH INTELLECTUAL DISABILITIES - Zahra Sativani; Mutiara Zahra Syahriani; Rovika Trioclarise (Universitas Negeri Gorontalo, 2026)
Background: Children with intellectual disabilities are at high risk of experiencing motor planning deficits, which impact their independence and social participation. These deficits are associated with impairments in sensory processing and sensorimotor integration. Although Sensory Integration Therapy (SIT) is widely used to improve motor skills in children with developmental disorders, research specifically evaluating the effectiveness of SIT on motor planning abilities in children with mild to moderate intellectual disabilities remains very limited. Most previous studies have focused on general motor skills or involved populations of children with other developmental disorders. Objective: To determine the effect of Sensory Integration Therapy on motor planning in children with intellectual disabilities at SLB Angkasa Halim in 2025. Methods: A quasi-experimental study using a two-group pretest-posttest design. The measurement tool used was the Bruininks-Oseretsky Test of Motor Proficiency, 2nd Edition, Short Form (BOT-2 SF). The intervention group received Sensory Integration Therapy three times a week for four weeks (40-minute sessions), while the control group engaged only in standard daily school activities. Results: Paired T-test results for the intervention group showed a mean value of 4.25 and a p-value of 0.000, whereas the control group showed a mean value of 0.41 and a p-value of 0.096. The Independent T-test yielded a p-value of 0.000, indicating a significant difference in the effect between the intervention and control groups. Conclusion: Sensory Integration Therapy has a significant effect on motor planning abilities in children with intellectual disabilities at SLB Angkasa.